2019
DOI: 10.1186/s41927-019-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Serious infections in patients with self-reported psoriatic arthritis from the Psoriasis Longitudinal Assessment and Registry (PSOLAR) treated with biologics

Abstract: BackgroundPatients with psoriatic arthritis (PsA) have increased risk of adverse events, including serious infections (SI), compared with psoriasis patients.MethodsPatients eligible for, or receiving conventional systemic and biologic agents for psoriasis were followed prospectively using PSOLAR. Cohorts included: ustekinumab, tumor necrosis factor (TNF) inhibitors; infliximab; etanercept; adalimumab; non-biologic/methotrexate (MTX) (reference group); and non-biologic/non-MTX. Multivariate analyses using Cox h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…There is little difference in general infection rates between drug and placebo groups in IL-17 and IL-23 antagonist studies (15). In the Psoriasis Longitudinal Assessment and Registry (PSOLAR), rates of serious infection were lower for ustekinumab than for psoriasis patients not on a biologic (16,17). For herpes zoster, in particular, rates were slightly higher, but there were few cases, and differences were not statistically significant (18).…”
Section: Should Patients Stop Their Biologic Treatment During the Covmentioning
confidence: 99%
“…There is little difference in general infection rates between drug and placebo groups in IL-17 and IL-23 antagonist studies (15). In the Psoriasis Longitudinal Assessment and Registry (PSOLAR), rates of serious infection were lower for ustekinumab than for psoriasis patients not on a biologic (16,17). For herpes zoster, in particular, rates were slightly higher, but there were few cases, and differences were not statistically significant (18).…”
Section: Should Patients Stop Their Biologic Treatment During the Covmentioning
confidence: 99%
“…In this record-linkage study, however, no effort was made to adjust the results for confounding by indication. This approach is necessary because glucocorticoid doses are linked to clinical activity, and increased disease activity is associated with an increased risk of infections in several rheumatic diseases [142][143][144][145][146][147] .…”
Section: Disease and Treatment Complicationsmentioning
confidence: 99%
“…Eder et al [ 101 ] reported that patients with PsA showed an increased risk of infection that required antibiotics (OR: 1.7; 95% CI: 1.00–2.77). As patients with PsA tend to receive more biologics than patients with psoriasis, they are at an increased risk of developing adverse events including infections [ 102 ]. The study by Haddad et al [ 103 ] also found that patients with PsA showed an increased incidence of infection than patients with psoriasis.…”
Section: The Risk Of Infection In Psoriasis and Psoriatic Arthritimentioning
confidence: 99%